ChemInform Abstract: Fe3O4/SiO2 Nanoparticles: An Efficient and Magnetically Recoverable Nanocatalyst for the One‐Pot Multicomponent Synthesis of Diazepines. Issue 5 (13th February 2013) - Maleki, Ali
Abstract The present new one‐pot multicomponent reaction of a diamine, a linear or cyclic ketone, and an isocyanide proceeds in the presence of a silica‐supported iron oxide catalyst affording diazepine derivatives in high yields.